Judicial Review of Article 27 (3) and (4) Law of the Republic of Indonesia Number 11 of 2008 (19 of 2016) Against the Criminalization of Advocates' Immunity Rights (Case Study: Advocate Alvin Lim, Advocate Kamaruddin Simanjutak and Advocate Prayitno) - Susilo, Budhi; Kian, Antonius Maria Laot; Leatemia, Philip Joseph (East Asian Journal of Multidisciplinary Research, 2024)
This research aims to study the degradation of advocates' immunity rights in Indonesia with special emphasis on Article 27 Paragraph (3) and Paragraph (4). This research is normative juridical in nature by using secondary data such as laws and regulations, court decisions, and other references to see the requirements of immunity rights, types of degradation caused by the Information and Transactions Electronic (ITE) Law, and factors that hinder and support immunity rights. The results of this research analysis are: First of all, the terms of advocates' immunity rights, which include the presence or absence of criminal and civil legal actions. If advocates carry out their work in an ethical manner, they will be protected, but ethical violations will be submitted to the Advocates Organization Code Council. Second, the cause of the reduction of advocates' immunity rights caused by Article 27 Paragraph (3) dan Paragraph (4) of the ITE Law identified that the effect of criminal and civil penalties can reduce the immunity rights of advocates in performing their professional duties. Third, the elements that hinder and support advocates' immunity rights are the functions of investigators, public prosecutors, judges, and public opinion.